Exchange rate pass-through to consumer prices: a European perspective - Michael Schröder; Felix P. Hüfner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
We study the pass-through of exchange rate changes to consumer prices for the euro area by estimating vector error correction models for Germany, France, Italy, the Netherlands and Spain. Using the weights of the Harmonized Index of Consumer Prices (HICP) we compute a weighted average of the country results for the euro area. We find that in response to a ten percent depreciation of the euro nominal effective exchange rate index, the HICP tends to increase by 0,4 percent after 12 months. The total effect amounts to 0,8 percent and the adjustment of consumer prices is completed after three years.
Keywords: E31; F31; F41; 330; pass-through; inflation; exchange rate; euro area; Exchange rate pass-through; Schätzung; Europäische Wirtschafts- und Währungsunion; Deutschland; Frankreich; Italien; Niederlande; Spanien